Improving transmission rate in WIMAX technology downlink - Al-Janabi H. D. (ХНУРЭ, 2013)
In this article presents mathematical model of sub-channels distribution in networks with standard IEEE 802.16, which provides a guaran-teed rate of user stations in downlink. Using various kinds of objective functions in offered model is directed to allocation of minimum data rate transmission of every user station. A comparative analysis of obtained solutions by using different objec tive functions was conducted.